A study on the impact of hair wrappings on yarn properties – Part I: Theoretical analysis and manual experimental validations. Issue 15 (September 2017) - Xia, Zhigang; Wu, Hui; Fu, Minghui; Ye, Wenxiang; Xu, Weilin
Hair-wrapping distribution, hair-wrapping direction and yarn moving direction models have been developed to analyze and predict the impact of hair wrappings on yarn properties in theory. Then, Nm 48 ring-spun ramie yarns were respectively treated by various manual hair wrappings, such as the forward diagonal, the forward vertical, the forward random, the backward diagonal, the backward vertical and the backward random. The results showed that the various hair-wrapped yarns had a similar smoothened static surface appearance. Although vertical hair wrappings caused the highest deterioration in yarn unevenness and imperfections, they kept the smallest change of hairiness among all types of hair wrappings during yarn moving. Hair wrapping contributed to large fiber utilization, improving yarn tensile properties, regardless of the worsened yarn unevenness and imperfections. The manual experimental results corresponded well to our modeling suppositions and theoretical analysis.